Crowdfunding as an Alternative to Property Development Financing in Disaster Management - Wisudanto, Wisudanto; Cahyolaksono, Narendro Bawono; Ardiyanto, Pramaditya; Kholiq, Mohamad Nur (STMIK Widya Cipta Dharma, 2024)
Crowdfunding is a collective fundraising process where a large number of people contribute funds to support a specific project, product, service, or cause. It utilizes digital platforms to connect fundraisers with funders, enabling the collection and distribution of funds in line with the advancements of the Industry 4.0 era. In particular, crowdfunding for natural disasters has proven to be an effective tool for raising funds to support post-disaster recovery efforts through social initiatives. This innovative approach has shifted societal behavior from being primarily consumptive to more productive, making it easier for donors to connect with meaningful and noble causes. Indonesia ranks as the most generous country in the 2024 World Giving Index, highlighting its strong culture of giving. This research aims to analyze whether crowdfunding can serve as an alternative funding mechanism for property development in disaster management and to identify its opportunities as an innovative and inclusive funding solution. The research methodology includes descriptive and literature studies. The findings conclude that crowdfunding holds significant potential as a social financing alternative for property development in disaster-affected areas. Moreover, it provides a platform for community engagement, enabling active participation in the post-disaster rehabilitation and reconstruction process through crowdfunding schemes.